MiR‐130b directly targets ARHGAP1 to drive activation of a metastatic CDC42‐PAK1‐AP1 positive feedback loop in Ewing sarcoma. Issue 10 (8th August 2017) - Satterfield, Laura; Shuck, Ryan; Kurenbekova, Lyazat; Allen‐Rhoades, Wendy; Edwards, Dean; Huang, Shixia; Rajapakshe, Kimal; Coarfa, Cristian; Donehower, Lawrence A.; Yustein, Jason T.
Abstract : Ewing Sarcoma (ES) is a highly aggressive bone tumor with peak incidence in the adolescent population. It has a high propensity to metastasize, which is associated with dismal survival rates of approximately 25%. To further understand mechanisms of metastasis we investigated microRNA regulatory networks in ES. Our studies focused on miR‐130b due to our analysis that enhanced expression of this microRNA has clinical relevance in multiple sarcomas, including ES. Our studies provide insights into a novel positive feedback network involving the direct regulation of miR‐130b and activation of downstream signaling events contributing toward sarcoma metastasis. Specifically, we demonstrated miR‐130b induces proliferation, invasion, and migration in vitro and increased metastatic potential in vivo . Using microarray analysis of ES cells with differential miR‐130b expression we identified alterations in downstream signaling cascades including activation of the CDC42 pathway. We identified ARHGAP1, which is a negative regulator of CDC42, as a novel, direct target of miR‐130b. In turn, downstream activation of PAK1 activated the JNK and AP‐1 cascades and downstream transcriptional targets including IL‐8, MMP1 and CCND1. Furthermore, chromatin immunoprecipitation of endogenous AP‐1 in ES cells demonstrated direct binding to an upstream consensus binding site within the miR‐130b promoter. Finally, small molecule inhibition of PAK1 blocked miR‐130b activation of JNK and downstream AP‐1 target genes, including primary miR‐130b transcripts, and miR‐130b oncogenic properties, thus identifying PAK1 as a novel therapeutic target for ES. Taken together, our findings identify and characterize a novel, targetable miR‐130b regulatory network that promotes ES metastasis. Abstract : What's new? Ewing sarcoma (ES) is an aggressive malignancy of bone with a tendency to metastasize, resulting in poor prognosis. Little is known, however, about the molecular mechanisms involved in metastatic ES. Here, enhanced expression of the microRNA miR‐130b was found to directly regulate ARHGAP1, a Rho‐type GTPase activating protein, in ES cells. Enhanced miR‐130b stimulated the CDC42/PAK1/AP‐1 axis, a pathway activated by Rho GTPase signaling, resulting in the activation of downstream targets, including AP‐1. AP‐1 bound directly to the miR‐130b promoter, fueling a positive feedback loop. The findings delineate a novel mechanism in sarcoma metastasis and reveal new therapeutic targets in ES.